A mosaic intragenic microduplication of LAMA1 and a constitutional 18p11.32 microduplication in a patient with keratosis pilaris and intellectual disability. Issue 11 (23rd September 2018) - Kashevarova, Anna A.; Nazarenko, Lyudmila P.; Skryabin, Nikolay A.; Nikitina, Tatiana V.; Vasilyev, Stanislav A.; Tolmacheva, Ekaterina N.; Lopatkina, Mariya E.; Salyukova, Olga A.; Chechetkina, Nataliya N.; Vorotelyak, Ekaterina A.; Kalabusheva, Ekaterina P.; Fishman, Veniamin S.; et al.
Abstract : The application of array‐based comparative genomic hybridization and next‐generation sequencing has identified many chromosomal microdeletions and microduplications in patients with different pathological phenotypes. Different copy number variations are described within the short arm of chromosome 18 in patients with skin diseases. In particular, full or partial monosomy 18p has also been associated with keratosis pilaris . Here, for the first time, we report a young male patient with intellectual disability, diabetes mellitus (type I), and keratosis pilaris, who exhibited a de novo 45‐kb microduplication of exons 4–22 of LAMA1, located at 18p11.31, and a 432‐kb 18p11.32 microduplication of paternal origin containing the genes METTL4, NDC80, and CBX3P2 and exons 1–15 of the SMCHD1 gene. The microduplication of LAMA1 was identified in skin fibroblasts but not in lymphocytes, whereas the larger microduplication was present in both tissues. We propose LAMA1 as a novel candidate gene for keratosis pilaris . Although inherited from a healthy father, the 18p11.32 microduplication, which included relevant genes, could also contribute to phenotype manifestation.